Anemia ferropriva na gestação: Controvérsias na suplementação do ferro - Modotti, Maria Teresa C.F.; Modotti, Cauê C.; Marcelino, Mônica Y. [UNESP]; De Oliva, Taís B.; Dias, Daniel S. [UNESP]; Dias, Flávia N.B. [UNESP]; Rodrigues, Natália Pavoni; Modotti, Waldir P. [UNESP] (My University, 2015)
The gestational period is associated with a series of physiological and anatomical modifications, such as changes in the hematological, respiratory and cardiovascular system. In addition to functional modifications, anemia due to iron deficiency stands out as one of the most common complications of pregnancy and depending on severity can cause harm to mother and/or fetus.The administration of iron for pregnant women, with or without a previous diagnosis of anemia, is a common practice in obstetrics. Although there's no evidence about the benefits of prophylactic iron supplementation for pregnant women, this approach appears as an appropriate procedure, since it reduces the prevalence of iron deficiency anemia during pregnancy and after childbirth. However, there are reports in the literature that describe the harmful aspects of indiscriminate use of iron during pregnancy. Thus, this literature review intend to present the main aspects of hematological changes that takes place during pregnancy, particularly iron deficiency anemia, to show advantages and disadvantages of iron supplementation, and to guide the obstetrician to perform a more accurate diagnosis of iron deficiency anemia during pregnancy. This literature also intend to propose a consistent alternative of iron supplementation for pregnant women, minimizing the undesirable risks of excess or deficiency of this supplementation.
Iron deficiency anemia in pregnancy: Controversies in iron supplementation
Keywords: Anemia, iron-deficiency; Clinical and laboratory diagnosis; Iron; Iron supplementation; Pregnancy